2012
DOI: 10.1063/1.4738956
|View full text |Cite
|
Sign up to set email alerts
|

Static surface temperature effects on the dissociation of H2 and D2 on Cu(111)

Abstract: A model for taking into account surface temperature effects in molecule-surface reactions is reported and applied to the dissociation of H(2) and D(2) on Cu(111). In contrast to many models developed before, the model constructed here takes into account the effects of static corrugation of the potential energy surface rather than energy exchange between the impinging hydrogen molecule and the surface. Such an approximation is a vibrational sudden approximation. The quality of the model is assessed by compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(123 citation statements)
references
References 61 publications
3
117
0
Order By: Relevance
“…No large non-adiabatic effects were found in these dynamics calculations, suggesting that the BornOppenheimer approximation works well for these systems. The validity of the static surface approximation has been tested recently for H 2 dissociation on Cu(111) using ab initio molecular dynamics (AIMD) calculations, 39 in which surface atoms in 3 layers of a 2 × 2 unit cell were allowed to move, and static corrugation model (SCM) calculations, 40 which excluded energy exchange with the surface but included the displacement of surface atoms and surface expansion effects. In these studies, good agreement was found between static surface calculations and calculations at the experimental surface temperature (T s = 120 K).…”
Section: A Dynamical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…No large non-adiabatic effects were found in these dynamics calculations, suggesting that the BornOppenheimer approximation works well for these systems. The validity of the static surface approximation has been tested recently for H 2 dissociation on Cu(111) using ab initio molecular dynamics (AIMD) calculations, 39 in which surface atoms in 3 layers of a 2 × 2 unit cell were allowed to move, and static corrugation model (SCM) calculations, 40 which excluded energy exchange with the surface but included the displacement of surface atoms and surface expansion effects. In these studies, good agreement was found between static surface calculations and calculations at the experimental surface temperature (T s = 120 K).…”
Section: A Dynamical Modelmentioning
confidence: 99%
“…The surface temperature used in the experiments, T s = 180 K, 31 is rather low. In ab initio molecular dynamics calculations 39 and static corrugation model calculations, 40 almost no effects were found for H 2 dissociating on Cu(111) at a surface temperature T s = 120 K. While the surface temperature for the molecular beam experiments on H 2 dissociation on Ru(0001) was slightly higher, the experimentalists did not find surface temperature effects down to T s = 140 K. 31 Furthermore, the lowest barriers in the H 2 on Ru(0001) system are further away from the surface than was the case for H 2 on Cu(111), suggesting a weaker coupling between H 2 and surface degrees of freedom. Finally, energy exchange is not expected to be important for this system due to the large mass mismatch between a H 2 molecule and a ruthenium atom.…”
Section: Scattering and Reaction At Off-normal Incidencementioning
confidence: 99%
“…We immediately note that the effect of surface temperature predicted by our model seems to be extremely small, clearly less than suggested by experiments [37,40] and by predictions of other theoretical models [41,62]. There are at least three problems that should be considered, that can explain the inadequacy of our model in reproducing the experimental results.…”
Section: Thermal Averagesmentioning
confidence: 64%
“…From the analysis of the energetic coupling, we pointed out in previous work that at least the motion of a first layer atom should be considered, both in the parallel and perpendicular direction. Furthermore, we cannot fully exclude the importance of non-additive couplings between the lattice degrees of freedom, even if they seem to be on a smaller energy scale [3] and even if the work by Wijzenbroek et al showed that a qualitatively consistent model for surface temperature can be built by simply considering uncoupled lattice atoms [62].…”
Section: Thermal Averagesmentioning
confidence: 99%
See 1 more Smart Citation